2022
DOI: 10.1093/icvts/ivac125
|View full text |Cite
|
Sign up to set email alerts
|

Sublobar resection versus lobectomy for patients with stage T1-2N0M0 pulmonary typical carcinoid tumours: a population-based propensity score matching analysis

Abstract: Objectives It is widely accepted that surgical resection of localized pulmonary typical carcinoid (TC) tumours remains the primary curative modality. However, the optimal extent of resection remains controversial. This study aimed to investigate the survival rates of patients with stage T1-2N0M0 TC tumours who underwent sublobar resection or lobectomy. Methods We queried the Surveillance, Epidemiology, and End Results databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 30 publications
(36 reference statements)
3
7
1
Order By: Relevance
“…When analyzed in the subgroup analysis stratified by surgical method, this survival trend was observed in patients who received lobectomy or sublobar resection and was consistent with the findings of previous studies. 5,14,15 However, in this study, we found that patients who received sublobar resection had fewer ELNs, compared with those who underwent lobectomy. The proportion of patients undergoing sublobar resection with ELNs < 4 was 80.18% (526/656), whereas for those undergoing lobectomy, this proportion decreased to 27.57% (435/1578).…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…When analyzed in the subgroup analysis stratified by surgical method, this survival trend was observed in patients who received lobectomy or sublobar resection and was consistent with the findings of previous studies. 5,14,15 However, in this study, we found that patients who received sublobar resection had fewer ELNs, compared with those who underwent lobectomy. The proportion of patients undergoing sublobar resection with ELNs < 4 was 80.18% (526/656), whereas for those undergoing lobectomy, this proportion decreased to 27.57% (435/1578).…”
Section: Discussioncontrasting
confidence: 57%
“…However, as surgical technologies continue to advance, the clinical application of sublobar resection has gradually increased. Moreover, studies 14,15 have increasingly confirmed that sublobar resection confers a noninferior survival benefit and safety compared with lobectomy in early-stage TCs. Moreover, TCs is an indolent tumor, which is less prone to LN and distant metastases and has good long-term survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations